Israel : Financial System Stability Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The Israeli financial system has been growing strong in the wake of a twin process of disinflation and structural transformation. The Bank of Israel plays a key role in liquidity management and absorbing liquidity shocks. All key financial sector activities, except payment systems, are satisfactorily supervised, though coordination among sectors should be improved. The paper also gives information of the Financial System Stability Assessment (FSSA) for Israel on compliance and consistency with international standards and codes relevant for the financial sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Israel